The effect of organizational culture transformation and talent management on organizational effectiveness mediated by job satisfaction - Imam Mahfud; Zakaria (Journal of Economics and Business Letters, 2021)
This study aims to determine the effect of Organizational Culture Transformation and Talent Management on Organizational Effectiveness mediated by Work. This research is based on organizational effectiveness in companies that have changed strategy due to encouragement from external industry factors so that organizational culture and talent management need to be carried out which are expected to increase organizational effectiveness. organization. The sample in this study was taken using a data collection method called purposive sampling. The sample used was 80 respondents. Data analysis using PLS (Partial Least Square) analysis technique through SmartPLS software. In addition, to test the hypothesis and the seventh, a trial was conducted to test the mediating/intervention variable in the hypothesis. The results showed that organizational culture transformation had a positive but not significant effect on organizational effectiveness. Furthermore, talent management has a positive and significant effect on organizational effectiveness. The results also show that the transformation of organizational culture and talent management has a positive but not significant effect on organizational effectiveness through job satisfaction owned by employees of PT. XYZ.